A prospective randomized clinical trial to evaluate the impact of intraoperative ventilation with high oxygen content on the extent of postoperative pneumocephalus in patients undergoing craniotomies. (4th March 2019) - Sandhu, G.; Gonzalez-Zacarias, A.; Fiorda-Diaz, J.; Soghomonyan, S.; Abdel-Rasoul, M.; Prevedello, L. M.; Uribe, A. A.; Stoicea, N.; Targonski, D.; Prevedello, D. M.; Bergese, S. D.
Abstract: Purpose of the article: To determine whether intraoperative ventilation with pure oxygen during the last stage of surgery reduces the occurrence and volume of postoperative pneumocephalus when compared to conventional air/oxygen mixture in patients undergoing craniotomy. Material and Methods: prospective randomized single-blinded study to compare the rate of occurrence and volume of postoperative pneumocephalus in patients undergoing craniotomy receiving intraoperative ventilation with pure oxygen (Group B) versus a conventional air/oxygen 1:1 mixture (Group A) during the last stage of surgery. This trial was registered in ClinicalTrials.gov #NCT02722928, protocol number 2015H0032. Results: One hundred patients were randomized into group 'A' and group 'B'. Seventy patients were included in the final analysis with 39 patients allocated in group 'A' and 31 patients in group 'B'. Median and IQR were used for postoperative penumocephalus volume. Group A: 9.65 [3.61–23.20]; Group B: 7.06 [2.70–20.1]. Our study showed no prophylactic effect on postoperative pneumocephalus volume when using mechanical ventilation with higher oxygen concentrations than the standard FiO2 during the last stage of surgery in patients undergoing craniotomy ( p  = .47). No statistical difference was found in SICU LOS between groups (median 1, 380 min [group A] versus 1, 524 min [group B]; p  = .18). Conclusion: The use of intraoperative mechanical ventilation with pure oxygen was not associated with a prophylactic effect on the occurrence and extent of postoperative pneumocephalus in our patient setting. Published literature describing the extent of postoperative pneumocephalus is limited or highly variable among institutions. Trial registration: ClinicalTrials.gov identifier: NCT02722928.